Digital Marketing Analysis in Dental Healthcare: The Role of Digital Marketing in Promoting Dental Health in the Community - Buyung Nazeli; Yudi Sugiarto; Ahyar Wahyudi (East Asian Journal of Multidisciplinary Research, 2023)
Modern marketing must integrate digital technology to enhance efficiency and effectiveness in communicating value to consumers. This research aims to uncover the impact of digital marketing strategies on the number of patients visiting dental clinics. Subsequently, it seeks to evaluate whether the implementation of digital marketing has a positive impact on the success of dental healthcare services. This research employs a survey approach with a descriptive method. Data shows that digital marketing has a significant impact on the number of patients visiting clinics compared to traditional patient acquisition methods. This underscores the importance of investing in digital marketing strategies to enhance the reach of dental healthcare services and attract more patients. Hence, internet marketing or digital marketing is not only a tool for modern marketing communication but also a highly influential tool in increasing patient numbers and expanding the scope of services in the context of dental healthcare.